Correction: Composition-dependent Raman modes of Mo1−xWxS2 monolayer alloys. Issue 37 (15th September 2016) - Chen, Yanfeng; Dumcenco, Dumitru O.; Zhu, Yiming; Zhang, Xin; Mao, Nannan; Feng, Qingliang; Zhang, Mei; Zhang, Jin; Tan, Ping-Heng; Huang, Ying-Sheng; Xie, Liming
Abstract : Correction for 'Composition-dependent Raman modes of Mo1− x W x S2 monolayer alloys' by Yanfeng Chen et al., Nanoscale, 2014, 6, 2833–2839.